2019
DOI: 10.1002/ajpa.23843
|View full text |Cite
|
Sign up to set email alerts
|

Household composition and the infant fecal microbiome: The INSPIRE study

Abstract: Objectives: Establishment and development of the infant gastrointestinal microbiome (GIM) varies cross-culturally and is thought to be influenced by factors such as gestational age, birth mode, diet, and antibiotic exposure. However, there is little data as to how the composition of infants' households may play a role, particularly from a cross-cultural perspective. Here, we examined relationships between infant fecal microbiome (IFM) diversity/composition and infants' household size, number of siblings, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 88 publications
(123 reference statements)
3
42
0
1
Order By: Relevance
“…core Gram negative bacteria in honey bees). 54 Similarly in humans, horizontal transfer of bifidobacteria and other bacteria from the environment and other household members likely contributes to the development of the infant gut microbiota, 55 regardless of breastfeeding. A fresh outlook based on principles of holobiont ecology 56 is required to better understand the functional importance of milk in vertical and horizontal bacterial transmission.…”
Section: Functional Importance Of Milk Microbiotamentioning
confidence: 99%
“…core Gram negative bacteria in honey bees). 54 Similarly in humans, horizontal transfer of bifidobacteria and other bacteria from the environment and other household members likely contributes to the development of the infant gut microbiota, 55 regardless of breastfeeding. A fresh outlook based on principles of holobiont ecology 56 is required to better understand the functional importance of milk in vertical and horizontal bacterial transmission.…”
Section: Functional Importance Of Milk Microbiotamentioning
confidence: 99%
“…Because geography is associated with lifestyle variation, we hypothesized (i) there would be differences in infant skin bacterial communities across the populations. More specifically, we expected that this variation would covary with variables related to socioeconomic status and household environments (38,40). Since different body sites harbor distinct microbial communities (17), we also hypothesized that (ii) there would be differences in the diversity of infant skin bacteria across the sampled skin sites.…”
mentioning
confidence: 99%
“…However, early life environments differ across human populations, suggesting that an infant's exposure to environmentally sourced microbes, including those from the social environment, may be highly variable across settings. For example, differences in childcare practices across sociocultural contexts could contribute to differential microbial exposures, including those related to attending daycare (36), hygiene practices (34), and physical contact with siblings or other caretakers (37)(38)(39)(40)(41)(42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, data are mixed as to whether the presence of siblings is associated with fecal microbial alterations. One study did not report a significant effect of prior sibling(s) on the clustering of the samples, while another reported that the number of siblings increased the abundance of Lactobacillus species in a linear manner . With that context, several studies have evaluated the association of maternal parity with JIA.…”
Section: Early Life Events and Jia Riskmentioning
confidence: 99%